Business Feasibility Analysis Of Pak Andri's Siomay And Batagor Business Reviewed From The Production Aspectp - Dona, Hesti Pestiko; Indriasari , Nia; Hardinata , Dodi (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the business feasibility of Pak Andri's Siomay and Batagor, to find out whether a business is feasible or not. The results of the research show that the Siomay and Batagor business from the production aspect of the business is declared feasible, because the business location is strategic and easy to reach by consumers, The technology used is modern, the production process is easy. The marketing aspect is feasible, with high quality products, because the raw materials are imported, the prices are affordable, so that all levels of society can buy them, the distribution is quite wide, and the promotions given by the owner are enough to make consumers aware of the products they sell.